Effect of Collection Date on Cone, Seed and Germination Characteristics in Himalayan Spruce [Picea smithiana (Wall.) Boiss.] - S.K. LAVANIA; VIRENDRA SINGH; R.P. SINGH (Seed Research, 2026)
The study deals with the effect of collection date on cone, seed and germination characteristics in Picea smithiana. The first cone collection was done on 15th September, second on 30th September, third on 15th October and fourth on 30th October from Gangotri range of Uttarkashi Forest Division of Garhwal Himalaya. Mean cone mid diameter increased from 15th September to 30th October while mean cone specific gravity decreased from first to fourth cone collection date. Percentage of viable seeds/cone increased while percentage of non-viable seeds/cone decreased with the maturity of cone. Mean fresh weight of 100 seeds increased from first cone collection date to fourth (last) cone collection date. The moisture content of seeds decreased while seed germination increased as cone collection dates progressed. Moisture content have significant negative correlation with germination percentage of seeds (r = -0.98). The maximum germination of seeds was obtained at the moisture content varying between 20.17 to 22.55 per cent. Germination per cent and germination value of seeds steadily increased from cone collection date of 15th September to 30th October. Therefore, the cones should be collected in the last week of October to obtain quality seeds.